2010
DOI: 10.1182/blood-2009-07-233270
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune B-cell lymphopenia after successful adoptive therapy with telomerase-specific T lymphocytes

Abstract: IntroductionAttempts to treat experimental tumors with adoptive T lymphocyte transfer started in 1960, soon after the demonstration that the cellular arm of the immune system was responsible for tissue rejection. 1 The translation of this approach to the clinic, however, became possible when human tumor-infiltrating lymphocytes (TILs) could be expanded in vitro and injected back into cancer patients. 2 Only recently, however, an objective cancer regression was achieved in approximately 50% of patients with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Despite these reports, several studies have reported mild to severe autoimmune toxicity following transfer of tumor reactive T cells (33)(34)(35) including liver toxicity in patients involving transfer of T cells gene-modified with an anti-CAIX scFv receptor (13). Toxicity, manifested by increased levels of transaminase in serum, was thought to be due to CAIX expression on bile duct epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these reports, several studies have reported mild to severe autoimmune toxicity following transfer of tumor reactive T cells (33)(34)(35) including liver toxicity in patients involving transfer of T cells gene-modified with an anti-CAIX scFv receptor (13). Toxicity, manifested by increased levels of transaminase in serum, was thought to be due to CAIX expression on bile duct epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, TCR can be isolated from mouse CTLs primed in vivo by vaccination of transgenic mice bearing human HLA-A2 molecules (14,15), an approach that was recently improved by the immunization of human antigen-negative mice engineered to bear the whole human TCR-a and b gene loci together with the HLA-A2 allele (16). We previously reported the feasibility to isolate and enrich a polyclonal T-cell population specific for human telomerase (hTERT) [865][866][867][868][869][870][871][872][873] epitope through in vitro stimulation of mouse T lymphocytes isolated from HLA-A2.1 transgenic mice (17). These CTLs recognized different hTERT-expressing human cancer cell lines, as well as colon cancer stem cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the feasibility to isolate and enrich a polyclonal T-cell population specific for human telomerase (hTERT) [865][866][867][868][869][870][871][872][873] epitope through in vitro stimulation of mouse T lymphocytes isolated from HLA-A2.1 transgenic mice (17). These CTLs recognized different hTERT-expressing human cancer cell lines, as well as colon cancer stem cells (17). Telomerase is reactivated in the majority of human tumors independently of their histology (18), and several hTERT epitopes, which are naturally processed and presented in association with MHC molecules on tumor cell surface, have been already documented (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The CD8 + T cells recognizing the self-antigen mTERT can treat established melanomas as effectively as T cells derived from Pmel-1 TCR transgenic mice, which recognize the hgp-100 melanoma antigen . However, melanoma growth control following ACT with both CD8 + T cells was achieved only in mice completely lacking adaptive immunity, lymphodepleted by nonmyeloablative irradiation, or pretreated with low doses of the chemotherapeutic drug 5-flourouracil (Ugel et al, 2012;Ugel et al, 2010). In normal hosts, mTERT-specific CD8 + T lymphocytes lack therapeutic efficacy and do not induce the appearance of Tip-DCs unless coupled with CSF-1R blockade.…”
Section: Discussionmentioning
confidence: 99%
“…To test this we used a model where CD8 + T cells have weak reactivity to their cognate antigen and fail to mediate anti-tumor effects in normal mice. We used mouse telomerase (mTERT)-specific CD8 + T cells, which lack anti-tumor activity against the TERT + MCA203 fibrosarcoma when used alone (Ugel et al, 2012;Ugel et al, 2010). Repeated administrations of anti-CSF-1R mAb with mTERT-specific CD8 + T cells on WT mice induced an additive delay in tumor growth ( Figure S6B and Figures 6B).…”
Section: Enhanced Act Efficacy Based On Supporting Tip-dc Functionmentioning
confidence: 99%